Import Competition and Gender Differences in Labor Reallocation - Hani Mansour; Pamela Medina; Andrea Velasquez (Institute of Labor Economics (IZA), 2020)
We study gender differences in the labor market reallocation of Peruvian workers in response to trade liberalization. The empirical strategy relies on variation in import competition across local labor markets based on their industrial composition before China entered the global market in 2001. We find that exposure to Chinese imports led to short-run declines in the employment share of women and men. However, the adverse employment effects are only persistent for women, leading to a reduction in their labor force participation. Lack of job market opportunities in the non-tradable sector act as a significant friction that prevents women from fully offsetting trade-induced displacements.
Keywords: E24; F14; J16; J71; 330; import competition; female employment; gender discrimination